2004
DOI: 10.1128/jb.186.15.5167-5171.2004
|View full text |Cite|
|
Sign up to set email alerts
|

The ompU Paralogue vca1008 Is Required for Virulence of Vibrio cholerae

Abstract: We made single and combined mutations in ompU, ompT, and the two putative porin genes vca1008 and vc0972. The fitness of the strains was tested in vitro and in the infant mouse model of intestinal infection. We also studied the transcriptional induction of vca1008 in vitro and during mouse infection. We show that vca1008 is induced during infection and is necessary and sufficient (in the absence of ompU, ompT, and vc0972) for infection.Vibrio cholerae is a gram-negative bacterium and facultative pathogen that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 20 publications
2
24
0
Order By: Relevance
“…This percentage (40%) is similar to the overall percentage (47%) of ivi genes that are required for virulence in animal models compiled from numerous IVET screening methods done on a number of different pathogens (1). Of the genes identified in this work, the most attenuated was VCA1008 (18). This result is interesting because VCA1008 was also the most highly induced ivi gene identified by our screening method.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…This percentage (40%) is similar to the overall percentage (47%) of ivi genes that are required for virulence in animal models compiled from numerous IVET screening methods done on a number of different pathogens (1). Of the genes identified in this work, the most attenuated was VCA1008 (18). This result is interesting because VCA1008 was also the most highly induced ivi gene identified by our screening method.…”
Section: Discussionsupporting
confidence: 69%
“…In this and a related study (18), we found that 7 of the 10 ivi genes tested were important to achieve wild-type levels of intestinal colonization. Three of these mutants were only mildly attenuated, whereas four were attenuated Ͼ10-fold.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Likewise, a Vibrio cholerae vca1008 mutant shows no defective growth in vitro. However, during infection of mice, the vca1008 mutant strain is severely outcompeted by the wild-type strain, indicating that the Vca1008 porin is necessary and sufficient for virulence, while OmpU is dispensable (192).…”
Section: Genes Involved In Cell Envelope Structure and Modificationmentioning
confidence: 99%
“…It was recently shown that the constitutively expressed M35 porin of Moraxella catarrhalis was required for growth under nutrient-limiting conditions (10). In contrast, OpnS was not required for growth under nutrient- (7,31,33,34). We show that the ⌬opnS strain was not attenuated for virulence against M. sexta since it killed the insect host as well as the wild-type strain by both direct injection and by natural infection with nematodes.…”
Section: Discussionmentioning
confidence: 80%